Blockchain-enabled food traceability system and consumers’ organic food consumption: A moderated mediation model of blockchain knowledge and trust in the organic food chain - Cong Doanh Duong; Thanh Tung Dao; Trong Nghia Vu; Thi Viet Nga Ngo; Minh Hoa Nguyen (Sustainable Futures)
Although the role of blockchain technology application in the organic food supply chain has been scholarly acknowledged, our understanding of how blockchain-enabled food traceability impacts consumer trust and purchase decisions is still limited. Adopting the lens from the stimulus-organism-response theory, this research draws a moderated mediation model to explore the direct and indirect impacts of blockchain-enabled food traceability system on organic food purchase behavior underlying a moderated mediation mechanism of blockchain knowledge and trust in the organic food chain. The PROCESS macro was approached using a purposive sample of 5,326 consumers in Vietnam to test the formulated hypotheses. The findings reveal that blockchain-enabled traceability significantly enhances trust in the organic food chain, which in turn positively influences organic food purchase behavior. Additionally, the study identifies blockchain knowledge as a crucial moderating factor, amplifying the direct and indirect effects of the traceability system on trust and purchase behavior. The study offers significant contributions to the literature by extending the application of the SOR model to technology-mediated environments and highlighting the role of consumer knowledge in moderating technology adoption outcomes. Some practical implications for practitioners are discussed.